Guiltily Indebted? How a Word Can Affect Individual Borrowing - Tamara Bogatzki; David Stadelmann; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2019)
Using World Values Survey data, we show that individuals whose primary language uses the same word for (financial) debt and (moral) guilt have a statistically significant and economically relevant lower probability of borrowing money. This relation holds even when we control for a large array of covariates, fixed effects, grammatical future tense reference, and Germanic language family.
Keywords: D14; D83; Z13; 330; economics of language; debts; borrowing; behaviour